2019
DOI: 10.5296/ijrd.v6i1.15292
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Impacts on Land Use and Land Cover Change in Ombeyi wetland, Kisumu County, Kenya

Abstract: Land use and land cover change as a result of human-induced transitions is a major environmental challenge in Lake Victoria Basin. The study adopted a mixed-method consisting of remote sensing and GIS-based analysis, key informant interviews, and household survey consisting of 384 households to asses Land Use and Land Cover Dynamics and associated human-induced transformations in Ombeyi wetland. The study aimed at generating a characterized area estimate of Ombeyi wetlands land use and land cover change schema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Using Landsat imageries, a combination of NDVI and NDWI indices were applied in land cover change detection of Tanguar Haor wetland, a Ramsar site in Bangladesh, in which it was established that about 40% of wetland cover had been converted to residential and agricultural land over 30 years period . In Kenya, remote sensing techniques have been used to assess land use/cover change detection in Rumuruti (Mwita, 2016), Nyando Wetland (Okotto-Okotto et al, 2018, and Ombeyi Wetland (Nicodemus et al, 2019) among other large wetlands. These studies cumulatively indicated that the landscape of Kenya's wetlands is actively transforming due to human-induced factors.…”
Section: Introductionmentioning
confidence: 99%
“…Using Landsat imageries, a combination of NDVI and NDWI indices were applied in land cover change detection of Tanguar Haor wetland, a Ramsar site in Bangladesh, in which it was established that about 40% of wetland cover had been converted to residential and agricultural land over 30 years period . In Kenya, remote sensing techniques have been used to assess land use/cover change detection in Rumuruti (Mwita, 2016), Nyando Wetland (Okotto-Okotto et al, 2018, and Ombeyi Wetland (Nicodemus et al, 2019) among other large wetlands. These studies cumulatively indicated that the landscape of Kenya's wetlands is actively transforming due to human-induced factors.…”
Section: Introductionmentioning
confidence: 99%
“…According to their findings, alterations in vegetation and water body extents had exacerbated the Isimangaliso Wetland Park's dramatic decrease in recent years. In Kenya, remote sensing techniques have been used to assess land use and land cover change detection in Rumuruti [14], Nyando Wetland [15], Tana River Basin [16], and Ombeyi Wetland [17] among other large wetlands. These studies cumulatively indicated that the landscape of Kenya's wetlands is actively transforming due to human-induced factors.…”
Section: Introductionmentioning
confidence: 99%
“…These images were processed using the producer company's Impact Observatory Deep-learning AI, trained using human-labeled image pixels developed by the United States National Geographic Society (Kontgis, 2022). As for the time frame the maps would be taken from, it would be annually for two (2) years before and after the implementation of the taxation policy of interest (Osoro, 2020;Redo et al, 2012). This means that the images that are to be considered in the study are within the years 2018 to 2021.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%